ALIENASI BURUH GALANGAN PT. EFRA DALAM KEHIDUPAN SOSIAL DI TANJUNGPINANG - Putri Agustina; Siti Arieta; Nanik Rahmawati (LPPM STISIP Persada Bunda, 2024)
This research aims to explore and further understand the forms of alienation experienced by the workers at PT Efra shipyard in their social, political, and cultural lives. The theory used in this study is the theory of alienation, which refers to the experience of individuals perceiving themselves as detached from the world. The process of alienation has transformed humans from creative subjects into passive objects in social processes. This study adopts a qualitative research design, conducted at PT Efra in Tanjungpinang. The informants were selected through purposeful sampling, considering their ability to provide the necessary information. Data were collected through observation, interviews, and documentation. The data analysis employed three stages: data reduction, data presentation, and conclusion/verification. The dinding of this research reveal that the workers at the shipyard experience alienation in their social lives, work environment, political engagement, and social interactions. Furthermore, the study identifies several job classifications that contribute to the workers' alienation at PT Efra based on their individual experiences. This research contributes to expanding the understanding of the phenomenon of worker alienation. It uncovers the factors causing alienation and its impact on the workers' social lives. The conclusion of the study indicates that the researchers themselves are alienated in four areas of life: social, political, and cultural, due to their work commitments, which prevent them from contributing to these aspects of life. The job types that most contribute to the workers' alienation are Fitter, Blasting, and Welder.